Abdominal Wall Allograft: Preclinical Biomechanical Investigation of a Novel Reconstructive Adjunct. (June 2017) - DeGeorge, Brent R.; Olenczak, Jonathan Bryce; Pineros-Fernandez, Angela; Morgan, Raymond F.; Cottler, Patrick S.; Drake, David B.
Abstract : Introduction: Acellular dermal matrices have revolutionized abdominal wall reconstruction; however, device failure and hernia recurrence remain significant problems. Fascia grafts are a reconstructive adjunct with increased tensile strength compared with acellular dermal matrices; however, clinical use is limited by insufficient donor material and donor site morbidity. To this end, we investigate the biomechanical properties of human abdominal wall allografts (AWAs) consisting of the anterior rectus sheath from xiphoid to pubis. Methods: After cadaveric procurement of 6 human AWAs, the tissue was divided horizontally and a matched-sample study was performed with specimens randomized to 2 groups: fresh, unprocessed versus processed with gamma irradiation and decellularization. Specimens were evaluated for physical properties, DNA content, tensile strength, and electron microscopy. Results: All AWA donors were male, with a mean age of 55.2 years (range, 35–74 years). Procured AWAs had a mean length of 21.70 ± 1.8 cm, width of 14.30 ± 1.32 cm, and area of 318.50 cm 2, and processing resulted in a 98.3% reduction in DNA content. Ultimate tensile strength was significantly increased after tissue processing, and after subcutaneous implantation, processed AWA demonstrated 4-fold increased tensile strength compared with unprocessed AWAs. Conclusions: Acellular AWAs represent a novel reconstructive adjunct for abdominal wall reconstruction with the potential of replacing "like with like" without additional donor site morbidity or antigenicity.